2013
DOI: 10.1016/j.biombioe.2013.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Ensiling as biological pretreatment of grass (Festulolium Hykor): The effect of composition, dry matter, and inocula on cellulose convertibility

Abstract: . (2013). Ensiling as biological pretreatment of grass (Festulolium Hykor): The effect of composition, dry matter, and inocula on cellulose convertibility. Biomass & Bioenergy, 58, 303-312. DOI: 10.1016/j.biombioe.2013 Our reference: JBB 3333 Dear Author, Please check your proof carefully and mark all corrections at the appropriate place in the proof (e.g., by using on-screen annotation in the PDF file) or compile them in a separate list. Note: if you opt to annotate the file with software other than Adobe Rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 20 publications
5
27
3
Order By: Relevance
“…The high TS content of the ensiled catch cropstraw blends (369e445 g L À1 ) probably resulted in energy loss due to respiration [14]. The values obtained for lactic acid content in the present study (data not shown) were 10 times lower than the values obtained by Ambye-Jensen et al [16]. The higher convertibility of the cellulose into free sugars during the ensiling process of grass (Festulolium) may be responsible of the high lactic concentration in that study.…”
Section: 3contrasting
confidence: 76%
“…The high TS content of the ensiled catch cropstraw blends (369e445 g L À1 ) probably resulted in energy loss due to respiration [14]. The values obtained for lactic acid content in the present study (data not shown) were 10 times lower than the values obtained by Ambye-Jensen et al [16]. The higher convertibility of the cellulose into free sugars during the ensiling process of grass (Festulolium) may be responsible of the high lactic concentration in that study.…”
Section: 3contrasting
confidence: 76%
“…In our previous study of the same grass species, ensiling directly improved the glucose yield from 7.8 to 11.4 (w/w)%. In the previous study it was concluded that the pretreatment effect was significantly influenced by the DM and biomass composition, which was distinguished by the relative maturity of the grass [18]. The data obtained in the present study supports that the particular grass cut has a significant influence on the effect of ensiling.The enzymatic hydrolysis experiments were performed repeatedly with different sample preparations.…”
Section: Resultssupporting
confidence: 86%
“…Most of the lignin concentrations were lower than the ones reported in literature, however a good variation in lignin content between the different substrates was still achieved. The lignin content of the ensilaged maize was very low (0.8 g/100 g) due to the ensilation process, which can be seen as a biological and prolonged acid pretreatment (Ambye-Jensen et al, 2013).…”
Section: Resultsmentioning
confidence: 99%